Pemberian Edukasi tentang Pubertas di Posyandu Remaja Pashmina di Kota Pekalongan - Maslikhah Maslikhah; Putri Andanawarih (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2023)
Adolescence is a period of storm and stress, as adolescents experience many challenges both from themselves (biopsychosocial factors) and the environment (environmental factors). If adolescents do not have the ability to deal with these challenges, they can end up with a variety of complex health problems as a result of their risky behavior. The complexity of health problems in adolescents, of course, requires comprehensive and integrated handling involving all elements from across related programs and sectors. The purpose of this community service is to provide education about puberty in adolescents. The method in this community service begins with a pre-test, namely distributing questionnaires about puberty in adolescents, in the form of closed questions totaling 10 questions, followed by material presentation delivered by 2 lecturers with a midwife background. There is an increase in knowledge about puberty in adolescents seen in the mean value which has an increase of 75.3% from a value of 2.3 to 9.3. The score from 68 to 280 experienced an increase of 75.7%. This proves that there is a positive increase after being given education about puberty in adolescents.